Analysis of milk trace elements with a home-made portable automated total reflection x-ray fluorescence system. (March 2019) - de Araújo, Ubiratan B.; da Costa, Ana Cristina M.; de Oliveira, Davi F.; de Jesus, Edgar F.O.; Anjos, Marcelino J.; Mársico, Eliane Teixeira; da Silva Carneiro, Carla; de Oliveira Resende Ribeiro, Roberta; Lopes, Ricardo T.
Abstract: This paper presents a portable, high-tech, low-cost, total reflection X-ray fluorescence system. This system features a compact arrangement consisting of a 50 W X-ray mini-tube with a Mo anode and a Si-PIN detector, quartz reflectors, lucite monochromator and micrometric tables driven by step motors controlled through the Arduino programming software. A certified sample of bovine liver SRM 1577b by NIST was used for the validation of the portable automated TXRF system. The TXRF system was used in the analysis of bovine milk samples collected in the industrialized region of the city of Bauru, São Paulo. In the analysis of the bovine milk samples the following elements were detected: P, S, K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Se, Rb and Sr. The TXRF portable automated system proved to be efficient, showing that it is possible to produce X-ray fluorescence with a low-cost system using a low-power X-ray tube and a compact Si-PIN detector. Highlights: A low cost portable automated TXRF system were developed. Bovine milk samples were analyzed through the TXRF portable system. Major and trace elements in bovine milk samples were quantified. The results obtained through this system are equivalent to the reported literature.